Phenotypic diversity of chickpea (Cicer arietinum L.) landraces accumulated in the Vavilov collection from the centers of the crop origin - M. A. Vishnyаkova; M. O. Burlyaeva; C. B. Bulyntsev; E. V. Seferova; E. S. Plekhanova; S. V. Nuzhdin (Вавиловский журнал генетики и селекции, 2017)
Chickpea (Cicer arietinum L.) is the second grain legume for the area of cultivation in the world, and the third for the production. However, modern cultivars of chickpea are typically susceptible to a variety of diseases, and have modest drought tolerance. The improvement of the crop for adaptability сould be carried out via introgression of valuable traits genes from old landraces collected in the centers of chickpea origin and diversity: the primary – Turkey and secondary – Ethiopia. The N.I. Vavilov All-Russian Institute of Plant Genetic Resources (thereafter VIR) preserves 3380 chickpea accessions, with landraces representing over a half of them. Here, the results of analysis of variability of 11 biological, morphological and economic-valuable traits in 1082 chickpea landraces descended from 60 countries are briefly driven. More in detail the sample of 75 landraces from Turkey and 24 landraces from Ethiopia (centres of chickpea origin) which had been sampled there 90 years ago have been studied. We analyzed the phenotypic variability with a treatment of 15 traits. The traits were studied using component analyses. Geographic regularities of certain traits in the studied accessions have been revealed. Ethiopian landraces are relatively homogeneous, belonging mostly to desi-type, and having fewer small, dark, and angular seeds, a short maturation period. They belong to the Abyssinian eco-geographical group, absolutely unique and endemic to Ethiopia. Turkish landraces are characterized by much higher diversity for the majority of phenotypes, covering almost the entire range of traits specified in chickpea descriptors. In this region, together with landraces typical for Turkey, there are those from the western Mediterranean and from the areas bordering with Turkey to the east. Landraces from primary and secondary centers of origin differed on the range of variability of the traits studied. The smaller degree of variation and primitiveness of the most traits and lower seed productivity in Ethiopian landraces in comparison with Turkish ones indicates a greater breeding advancement of the latter. Useful traits for breeding are present in the landraces from both centers of origin and diversity.